2011
DOI: 10.1146/annurev-ento-120709-144823
|View full text |Cite
|
Sign up to set email alerts
|

Insect Seminal Fluid Proteins: Identification and Function

Abstract: Seminal fluid proteins (SFPs) produced in reproductive tract tissues of male insects and transferred to females during mating induce numerous physiological and behavioral post-mating changes in females. These changes include decreasing receptivity to re-mating, affecting sperm storage parameters, increasing egg production, modulating sperm competition, feeding behaviors, and mating plug formation. In addition, SFPs also have anti-microbial functions and induce expression of anti-microbial peptides in at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
884
1
16

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 806 publications
(917 citation statements)
references
References 172 publications
16
884
1
16
Order By: Relevance
“…In addition, relative to virgin females, inseminated females have increased egg development and oviposition rates. These changes in inseminated females appear to be induced by molecules produced in male accessory glands and transferred to the female during mating as suggested by Avila et al (2010) and recently confirmed for An. gambiae (Thailayil et al 2011).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, relative to virgin females, inseminated females have increased egg development and oviposition rates. These changes in inseminated females appear to be induced by molecules produced in male accessory glands and transferred to the female during mating as suggested by Avila et al (2010) and recently confirmed for An. gambiae (Thailayil et al 2011).…”
Section: Discussionmentioning
confidence: 56%
“…During copulation, the male deposits a mixture of sperm and accessory gland secretion in the female's bursa copulatrix, causing the female to become unreceptive to other males. Male seminal fluid proteins have been shown to influence female reproductive and feeding behaviours in many insects (reviewed in Gillot 2003, Avila et al 2010). In addition, relative to virgin females, inseminated females have increased egg development and oviposition rates.…”
Section: Discussionmentioning
confidence: 99%
“…For female insects, mating often induces large transcriptional, physiological and behavioural changes that are often triggered by components of male seminal fluid (Avila et al, 2011). These changes and the molecules that cause them have been studied in detail in Drosophila melanogaster (Findlay et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that AG secretion might activate sperm to facilitate transfer to the queen's spermatheca (Poiani, 2006;Smith and Stanfield, 2012). AG secretion could also be transferred first to interact with the female environment before the arrival of sperm, for example to eliminate traces of microbial pathogens that might reside there, as seminal fluid has been shown to contain antimicrobial proteins in a number of insects and mammals (Avila et al, 2011;Baer et al, 2009b;Poiani, 2006). In addition, AG secretion could form a temporary barrier between sperm and ejaculates of rival males already present in the reproductive tract of the queen, to delay potential harmful effects.…”
Section: Reconstructing the Dynamics Of Sperm Competition In Antsmentioning
confidence: 99%